The Effect of Self Help Group Intervention on Life Satisfaction of Elderly with Hypertension - Suryadin, Asep; Nurharlinah, Nurharlinah; Murtiningsih, Murtiningsih; Inayah, Iin; Ropei, Oop (Journal La Medihealtico, 2024)
The increasing age of the elderly will affect the ability to respond to stressors originating from oneself and the environment outside the elderly. The increasing age of the elderly causes various problems both physical, biological, mental, socio-economic and life satisfaction in the elderly. So this can be minimized with community empowerment activities, one of which is a self-help group (SHG). The aim of this research is to identify the effect of self-help group intervention on life satisfaction of elderly people with hypertension in the Nagrak Community Health Center working area, Cianjur Regency. This research is quantitative research using a quasi-experimental design with a Pretest – Posttest two Group Design approach. The sample was taken using a total sampling technique, namely 36 respondents. This research was analyzed using the independent t test. Based on the research results, the results of statistical tests using the Independent Samples Test show that the resulting P value is 0.000<0.05. So it can be concluded that there is an influence of the self-help group on the life satisfaction of the elderly in the treatment group after the self-help group intervention was carried out in the work area of the Nagrak Community Health Center, Cianjur Regency. Suggestion: future researchers can measure confounding variables as a whole, for example spiritual factors, family support, recreation and others.